Two Parallel Olfactory Pathways for Processing General Odors in a Cockroach - Watanabe, Hidehiro; Nishino, Hiroshi; Mizunami, Makoto; Yokohari, Fumio (Frontiers in Neural Circuits, 2017)
In animals, sensory processing via parallel pathways, including the olfactory system, is a common design. However, the mechanisms that parallel pathways use to encode highly complex and dynamic odor signals remain unclear. In the current study, we examined the anatomical and physiological features of parallel olfactory pathways in an evolutionally basal insect, the cockroach Periplaneta americana. In this insect, the entire system for processing general odors, from olfactory sensory neurons (OSNs) to higher brain centers, is anatomically segregated into two parallel pathways. Two separate populations of secondary olfactory neurons, type1 and type2 projection neurons (PNs), with dendrites in distinct glomerular groups relay olfactory signals to segregated areas of higher brain centers. We conducted intracellular recordings, revealing olfactory properties and temporal patterns of both types of PNs. Generally, type1 PNs exhibit higher odor-specificities to nine tested odorants than type2 PNs. Cluster analyses revealed that odor-evoked responses were temporally complex and varied in type1 PNs, while type2 PNs exhibited phasic on-responses with either early or late latencies to an effective odor. The late responses are 30-40 milliseconds later than the early responses. Simultaneous intracellular recordings from two different PNs revealed that a given odor activated both types of PNs with different temporal patterns, and latencies of early and late responses in type2 PNs might be precisely controlled. Our results suggest that the cockroach is equipped with two anatomically and physiologically segregated parallel olfactory pathways, which might employ different neural strategies to encode odor information.